2016
DOI: 10.1007/s00394-016-1317-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in glucose tolerance and insulin sensitivity by probiotic strains of Indian gut origin in high-fat diet-fed C57BL/6J mice

Abstract: Native probiotic strains MTCC 5690 and MTCC 5689 appear to have potential against insulin resistance and type 2 diabetes with mechanistic, multiple tissue-specific mode of actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
130
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(156 citation statements)
references
References 57 publications
10
130
1
7
Order By: Relevance
“…In the present study, the glucose tolerance was unimpaired and the huge increases in HOMA‐IR was abrogated in HFD/STZ‐T2DM rats fed on L. paracasei NL41, suggesting that oral administration of live probiotic strain NL41 could prevent or delay the onset of T2DM by ameliorating insulin resistance. Previous studies have reported that a diet supplemented with L. casei strain CCFM419 increases glucose tolerance in HFD/STZ‐induced T2DM rats, L. rhamnosus GG improves glucose tolerance in STZ‐induced diabetic rats and that the impaired glucose tolerance in HFD‐fed mice is alleviated by L. fermentum strain MTCC 5689 administration, consistent with our studies. PI3K/Akt signalling pathway plays a crucial role in insulin action to regulate glucose and lipid metabolism and a long‐term HFD blunts this pathway .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the glucose tolerance was unimpaired and the huge increases in HOMA‐IR was abrogated in HFD/STZ‐T2DM rats fed on L. paracasei NL41, suggesting that oral administration of live probiotic strain NL41 could prevent or delay the onset of T2DM by ameliorating insulin resistance. Previous studies have reported that a diet supplemented with L. casei strain CCFM419 increases glucose tolerance in HFD/STZ‐induced T2DM rats, L. rhamnosus GG improves glucose tolerance in STZ‐induced diabetic rats and that the impaired glucose tolerance in HFD‐fed mice is alleviated by L. fermentum strain MTCC 5689 administration, consistent with our studies. PI3K/Akt signalling pathway plays a crucial role in insulin action to regulate glucose and lipid metabolism and a long‐term HFD blunts this pathway .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a meta-analysis suggests that the supplementation of probiotics has a modest effect on the serum level of fasting blood sugar as well as oxidative stress biomarkers [211]. Mechanisms that have been proposed are as follows: improved intestinal integrity, decreased systemic lipopolysaccharide levels, decreased endoplasmic reticulum stress and improved peripheral insulin sensitivity [204,212]. Data from clinical studies and animal models have shown a reduction in lipopolysaccharide translocation, endotoxemia and inflammation, reducing stimulation of the proinflammatory genes like tumor necrosis factor alpha (TNF-α), IL-6 and IL-1β [204,213].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…This microbiota transfer could alter the microbial community in the upper small intestine, contributing to this insulin-sensitizing effect. Similarly, pre-and probiotics improve glucose regulation and robustly alter distal intestinal and fecal microbiota of rodents and humans (Balakumar et al, 2016;Cani et al, 2006a;Ejtahed et al, 2012;Everard and Cani, 2013); however, these substances must first pass the upper small intestine where they could elicit their glucoregulatory effects. This is in line with the fact that most probiotics are derived from Lactobacillus (Asemi et al, 2013;Balakumar et al, 2016;Ejtahed et al, 2012;Yadav et al, 2007), which is a prominent inhabitor of the small intestine (Gu et al, 2013;Wirth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%